1999
DOI: 10.1200/jco.1999.17.3.761
|View full text |Cite
|
Sign up to set email alerts
|

Phase II Trial of Paclitaxel and Cisplatin in Metastatic and Recurrent Carcinoma of the Uterine Cervix

Abstract: The combination of paclitaxel with cisplatin seems relatively well tolerated and moderately active in patients with metastatic or recurrent cervical cancer. The significant incidence of neurotoxicity is of concern, and alternative methods of administration of the two agents could be evaluated. Then, further study of this combination, alone or with the addition of other active agents, is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
51
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 99 publications
(56 citation statements)
references
References 25 publications
4
51
1
Order By: Relevance
“…Several combination chemotherapy regimens that contain cisplatin have been tested in phase II studies, and objective responses have been documented in 30 -70% of the patients, while the median overall survival time ranged between 7 and 12 months (Buxton et al, 1989;Murad et al, 1994;Long et al, 1995;Papadimitriou et al, 1997Papadimitriou et al, , 1999Rose et al, 1999). Although it is difficult to directly compare the relative merits of the combined regimens with the single agents, combination chemotherapy seems to be superior to single-agent therapy based on these phase II studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several combination chemotherapy regimens that contain cisplatin have been tested in phase II studies, and objective responses have been documented in 30 -70% of the patients, while the median overall survival time ranged between 7 and 12 months (Buxton et al, 1989;Murad et al, 1994;Long et al, 1995;Papadimitriou et al, 1997Papadimitriou et al, , 1999Rose et al, 1999). Although it is difficult to directly compare the relative merits of the combined regimens with the single agents, combination chemotherapy seems to be superior to single-agent therapy based on these phase II studies.…”
Section: Discussionmentioning
confidence: 99%
“…Many combination chemotherapy regimens have also been explored during the last two decades. High response rates have been obtained in some studies, but it is difficult to assess the relative merits of the various regimens because of differences in patient selection (Buxton et al, 1989;Papadimitriou et al, 1999).…”
mentioning
confidence: 99%
“…However, if CHFR is inactive, damaged DNA cannot be repaired and continuation of somatic cell division leads to apoptosis and increased sensitivity to paclitaxel. Cervical adenocarcinoma has lower sensitivity to anticancer agents compared with cervical SCC (9), and has higher sensitivity to these agents if CHFR is epigenetically suppressed (10). Thus, the aberrant hypermethy lation of CHFR in cervical adenocarcinoma is a candidate biomarker for sensitivity to paclitaxel.…”
Section: Biomarkers Associated With Sensitivity To Anticancer Agentsmentioning
confidence: 99%
“…The rationales of using paclitaxel in combination with cisplatin in concurrent chemoradiation are that 1) paclitaxel acts as a radiosensitizer in vitro, 7,8 2) a phase I study with cisplatin plus paclitaxel has proved excellent overall response in patients with locally advanced cervical cancer, 9 and 3) cisplatin plus paclitaxel have activity against metastatic and recurrent cervical cancer. 10 Recently, several studies which used cisplatin plus paclitaxel with concurrent radiation have been reported. 9,[11][12][13] These were phase I and/or II studies which focused on evaluating toxicities and response rates in a limited number of enrolled patients.…”
Section: Introductionmentioning
confidence: 99%